2019
DOI: 10.1002/jcp.28981
|View full text |Cite
|
Sign up to set email alerts
|

Mu‐KRAS attenuates Hippo signaling pathway through PKCι to sustain the growth of pancreatic cancer

Abstract: The atypical protein kinase C isoform ι (PKCι) is upregulated, which cooperates with mutated KRAS (mu-KRAS) to promote the development of pancreatic cancers.However, the exact role of PKCι in KRAS-mediated pancreatic tumorigenesis is not fully defined. In the present study, we demonstrate that mu-KRAS upregulates and activates PKCι, accompanied by dephosphorylation of large tumor suppressor (LATS), a key member of the growth-inhibiting Hippo signaling pathway. As a result, Yes-associated protein 1 (YAP1; a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Similar to RIPK2, PRKCI also has a higher expression in PC tissues than the normal, and a higher PRKCI expression predicts a poorer survival of PC patients. The oncogenic role of PRKCI-encoding protein PKC iota has been well established, recent studies in PC suggested that mutated KRAS can elevate and activate PKC iota to disable growth-inhibitory Hippo signaling and promote Yes-associated protein1 (YAP-1) translocation into nucleus, and thus maintain PC cells growth (Wang et al 2020 ). Also, PKC iota upregulates transcription factor specificity protein 1 to promote transactivation of YAP-1 and induce tumorigenesis (Yang et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to RIPK2, PRKCI also has a higher expression in PC tissues than the normal, and a higher PRKCI expression predicts a poorer survival of PC patients. The oncogenic role of PRKCI-encoding protein PKC iota has been well established, recent studies in PC suggested that mutated KRAS can elevate and activate PKC iota to disable growth-inhibitory Hippo signaling and promote Yes-associated protein1 (YAP-1) translocation into nucleus, and thus maintain PC cells growth (Wang et al 2020 ). Also, PKC iota upregulates transcription factor specificity protein 1 to promote transactivation of YAP-1 and induce tumorigenesis (Yang et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…PKCι is upregulated and activated in pancreatic cancers with mutated KRAS, resulting in increased dephosphorylation and nuclear translocation of YAP1. These changes promote the growth of pancreatic cancer [ 248 ]. Inhibition of PKCι alone [ 249 ] or in combination with other inhibitors (e.g., specificity protein 1 (Sp1) inhibitor) [ 250 ] reduced cell growth and metastasis and induced apoptosis in pancreatic cancer cells.…”
Section: Pkc Isozymes As Prognostic Biomarkers or Therapeutic Targets...mentioning
confidence: 99%
“…Furthermore, in breast cancer cells, knockout of POPX2 impaired anchorage-independent growth [60]. Inactivation of LATS by dephosphorylation in pancreatic cancer is caused by PKCiota cooperation with mutant KRas [61], both of which are up-regulated in PC and associated with disease progression [62].…”
Section: Post-translation Repression Of Lats1/2mentioning
confidence: 99%